The Role Of The Financial Services Authority (OJK) In Fostering And Supervising The Insurance Industry Associated With The Availability Of OJK Contributions In Indonesia's Economic Development Construction - Marihot SIMANJUNTAK; Wiwik Sri WIDIARTY (International Journal of Environmental, Sustainability, and Social Science, 2022)
Insurance companies as risk transfer and sharing institutions have positive benefits for society, companies, and state development. In Indonesia, insurance is one of the supports for the pace of the economy which is supervised by the Financial Services Authority (OJK). Another issue is that the insurance business cannot be separated from the issue of fraud or insurance fraud. Fraud in insurance can be done starting from the bidding/registration process to submitting a claim to get financial benefits. The ghost of fraud threatens insurance in Indonesia. In Indonesia, there are several legal cases of non-payment of insurance, such as Bumiputera 1912 Life Insurance worth 12 trillion rupiahs, Jiwasraya Insurance 17 trillion rupiahs and ASABRI 15 trillion rupiahs, for which until now there has not been the most appropriate solution. The approach method used in this research is normative juridical, and the type of research chosen is descriptive analysis. Claim settlement mechanism. The results of the study stated that the Insurance Industry industry must be canceled and dissolved. it is recommended that if it is difficult to use APBN funds, then the functions and supervision of the OJK are returned to their original functions, so that there will be no more defaults, due to the negligence of the OJK who is busy collecting the OJK. Mandatory Contribution up to a fine/penalty if late payment.